Biological effects of magnetic fields emitted by graphene devices, on induced oxidative stress in human cultured cells - Franceschelli, Sara; D’Andrea, Pierdomenico; Speranza, Lorenza; De Cecco, Federica; Paolucci, Teresa; Panella, Valeria; Grilli, Alfredo; Benedetti, Stefano (Frontiers in Bioengineering and Biotechnology, 2024)
Many recent studies have explored the healing properties of the extremely low-frequency electromagnetic field (ELF-EMF) to utilize electromagnetism for medical purposes. The non-invasiveness of electromagnetic induction makes it valuable for supportive therapy in various degenerative pathologies with increased oxidative stress. To date, no harmful effects have been reported or documented. We designed a small, wearable device which does not require a power source. The device consists of a substrate made of polyethylene terephthalate and an amalgam containing primarily graphene nanocrystals, also known as quantum dots. This device can transmit electromagnetic signals, which could induce biological effects. This study aims to verify the preliminary effects of the electromagnetic emission of the device on leukemic cells in culture. For this purpose, we studied the best-known effects of magnetic fields on biological models, such as cell viability, and the modulations on the main protagonists of cellular oxidative stress.